Plato and Liberalism - Bagnulo, V; Vince Bagnulo (2009)
Plato is generally regarded as notoriously anti-liberal, a reputation which is based mainly upon his most famous political work, the Republic. However, a more comprehensive view of his political thought reveals a much more nuanced picture. In this essay, I offer a comparison between modern liberalism and Plato's political thought, as presented in his three major political dialogues, the Republic, the Statesman, and the Laws, on the topic of freedom, as well as four secondary topics: (1) rule of law (2) legal reform (3) consent of the ruled (4) democracy. I begin with a brief account of modern liberalism and then proceed to evaluate each of the three dialogue on the above five topics. Although Plato's most famous political work, it is here argued that the Republic says surprisingly little on all these topics other than freedom because several of its most prominent proposals, including its famous philosopher-rulers, are not presented for implementation in actual politics. The Statesman, the briefest of the three, is argued to exhort rule of law and legal reform, but say little on the other topics. The most space will be dedicated to the Laws, which will be shown to offer detailed comment on each topic. The city the Laws depicts will be argued to be not one in which a docile citizenry is ruled over by an Inquisitorial Nocturnal Council, but a city ruled by law which cultivates the rational capacities of its citizens, who are thoroughly involved in government. However, this city will also prove to be one in which strong restrictions are placed on the sorts of freedoms that liberalism values. On the four secondary topics, Plato's thought will be argued to be largely in agreement with modern liberalism. However, on freedom it will be argued there is large disagreement, with Plato shown to attach little value to the liberal notion of freedom, though taking freedom very seriously in his own right.